Differences in spontaneous speech fluency between Parkinson's disease and spinocerebellar ataxia type 3 - dos Santos, Vanessa Brzoskowski; Ayres, Annelise; Kieling, Maiara Laís Mallmann; Miglorini, Elaine Cristina; Jardim, Laura Bannach; Schumacher-Schuh, Artur Francisco; Rieder, Carlos Roberto de Mello; Castilhos, Raphael Machado de; Spencer, Kristie; Rothe-Neves, Rui; Olchik, Maira Rozenfeld (Frontiers in Neurology, 2023)
Background The basal ganglia and cerebellum both have a role in speech production although the effect of isolated involvement of these structures on speech fluency remains unclear. Objective The study aimed to assess the differences in the articulatory pattern in patients with cerebellar vs. basal ganglia disorders. Methods A total of 20 individuals with Parkinson's disease (PD), 20 with spinocerebellar ataxia type 3 (SCA3), and 40 controls (control group, CG) were included. Diadochokinesis (DDK) and monolog tasks were collected. Results The only variable that distinguished SCA3 carriers from the CG was the number of syllables in the monolog, with SCA3 patients of a significantly lower number. For patients with PD, the number of syllables, phonation time, DDK, and monolog were significantly lower than for CG. Patients with PD were significantly worse compared to patients with SCA3 in the number of syllables and phonation time in DDK, and phonation time in monolog. Additionally, there was a significant correlation between the number of syllables in the monolog and the MDS-UPDRS III for participants with PD, and the Friedreich Ataxia Rating Scale for participants with SCA3 suggesting a relationship between speech and general motor functioning. Conclusion The monolog task is better at discriminating individuals with cerebellar vs. Parkinson's diseases as well as differentiating healthy control and was related to the severity of the disease.